ERα suppresses slug expression directly by transcriptional repression - Ye, Yin (Portland Press Ltd., 2008)
Two of the most common signalling pathways in breast cancer are the ER (oestrogen receptor) ligand activation pathway and the E-cadherin snai1 slug EMT (epithelial–mesenchymal transition) pathway. Although these pathways have been thought to interact indirectly, the present study is the first to observe direct interactions between these pathways that involves the regulation of slug expression. Specifically we report that ligand-activated ERα suppressed slug expression directly by repression of transcription and that knockdown of ERα with RNA interference increased slug expression. More specifically, slug expression was down-regulated in ERα-negative MDA-MB-468 cells transfected with ERα after treatment with E2 (17β-oestradiol). The down-regulation of slug in the ERα-positive MCF-7 cell line was mediated by direct repression of slug transcription by the formation of a co-repressor complex involving ligand-activated ERα protein, HDAC1 (histone deacetylase 1) and N-CoR (nuclear receptor co-repressor). This finding was confirmed by sequential ChIP (chromatin immunoprecipitation) studies. In the MCF-7 cell line, slug expression normally was low. In addition, knockdown of ERα with RNA interference in this cell line increased slug expression. This effect could be partially reversed by treatment of the cells with E2. The efficacy of the effect of ERα on slug repression was dependent on the overall level of ERα. These observations confirmed that slug was an E2-responsive gene.